Potentiometric Study of Binary and Ternary Complexes of Some Bivalent Transition Metal Ions with Some Pharmaceutical Compounds - Patil, A.B.; Mhaske, T.H. (Asian Journal of Chemistry, 2010)
To explore the complexing tendency of some 3d metal ions the binary and ternary complexation tendencies of Mn(II), Co(II), Ni(II), Cu(II) and Zn(II) were studied by the pH-metric technique at the ionic strength 0.1 M (KNO3) and the temperature 29 ± 0.5ºC in aqueous medium. The metal-ligand stability constants of binary complexes were evaluated using Irving-Rossotti titration technique and the metal-ligand stability constants using primary ligands nitrilotriacetic acid (NTA) and iminodiacetic acid (IMDA) and the drugs pyridoxine hydrochloride (PHC) and ethambutol hydrochloride (EHC) as secondary ligands were evaluated at the same conditions using modified form of Irving-Rossotti technique.